2010
DOI: 10.1111/j.1468-1293.2010.00885.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, tolerability and risk factors for virological failure of darunavir-based therapy for treatment-experienced HIV-infected patients: the Swiss HIV Cohort Study

Abstract: Objectives Darunavir was designed for activity against HIV resistant to other protease inhibitors (PIs). We assessed the efficacy, tolerability and risk factors for virological failure of darunavir for treatment-experienced patients seen in clinical practice. Methods We included all patients in the Swiss HIV Cohort Study starting darunavir after recording a viral load above 1000 HIV-1 RNA copies/mL given prior exposure to both PIs and nonnucleoside reverse transcriptase inhibitors. We followed these patients f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
0
15
0
2
Order By: Relevance
“…We then assigned wide log-normal distributions to each category such that these distributions reduced the probability of extreme hazard ratios (HRs; Supplementary Table 2). We used a prior HR of 1.5 (95% credible interval [CrI], 0.38–6.0) for possibly harmful risk factors, 2.0 (95% CrI, 0.5–8.0) for probably harmful risk factors, 1.0 (95% CrI, 0.25–4.0) for factors of uncertain direction, and 0.69 (95% CrI, 0.17–2.7) for possibly protective risk factors [20, 23]. We used R 3.1.0, R2WinBUGS 2.1–20 and WinBUGS 1.4.3 for our analysis.…”
Section: Methodsmentioning
confidence: 99%
“…We then assigned wide log-normal distributions to each category such that these distributions reduced the probability of extreme hazard ratios (HRs; Supplementary Table 2). We used a prior HR of 1.5 (95% credible interval [CrI], 0.38–6.0) for possibly harmful risk factors, 2.0 (95% CrI, 0.5–8.0) for probably harmful risk factors, 1.0 (95% CrI, 0.25–4.0) for factors of uncertain direction, and 0.69 (95% CrI, 0.17–2.7) for possibly protective risk factors [20, 23]. We used R 3.1.0, R2WinBUGS 2.1–20 and WinBUGS 1.4.3 for our analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Weakly informative priors restrict covariate effects to a range of values that is clinically sensible, ruling out extreme values that no knowledgeable clinician would find plausible [15]. The effects of genotype 3 and of genotypes other than 1 or 3 were both assumed to be of ‘uncertain direction’ (prior odds ratio (OR) 1.0, 95% credible interval (CI) 0.25 to 4.0); no prior treatment was assumed to be ‘possibly beneficial’ (prior OR 1.5, 95% CI 0.38 to 6.0); and no or stable cirrhosis was assumed to be ‘probably beneficial’ (prior OR 2.0, 95% CI 0.5 to 8.0) [16, 17]. There is clinical interest in the value of including ribavirin in treatment combinations but limited information [18, 19].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the Swiss Cohort Study reported that as a component of therapy for treatment-experienced patients, DRV/r could achieve a similar efficacy and tolerability in clinical practice to those seen in clinical trials. Clinicians should consider whether a patient has failed treatment with both lopinavir and saquinavir and the number of failed PI regimens before prescribing darunavir [ 7 ]. In Brazil, a cohort study was conducted with DRV/r plus an OBR and found that it was a highly effective salvage regimen under clinical routine conditions [ 8 ].…”
Section: Introductionmentioning
confidence: 99%